Draft genomic sequence of a chromate- and sulfate-reducing Alishewanella strain with the ability to bioremediate Cr and Cd contamination. Issue 1 (December 2016) - Xia, Xian; Li, Jiahong; Liao, Shuijiao; Zhou, Gaoting; Wang, Hui; Li, Liqiong; Xu, Biao; Wang, Gejiao
Abstract Alishewanella sp. WH16-1 (= CCTCC M201507) is a facultative anaerobic, motile, Gram-negative, rod-shaped bacterium isolated from soil of a copper and iron mine. This strain efficiently reduces chromate (Cr6+ ) to the much less toxic Cr3+ . In addition, it reduces sulfate (SO4 2− ) to S2− . The S2− could react with Cd2+ to generate precipitated CdS. Thus, strain WH16-1 shows a great potential to bioremediate Cr and Cd contaimination. Here we describe the features of this organism, together with the draft genome and comparative genomic results among strain WH16-1 and otherAlishewanella strains. The genome comprises 3, 488, 867 bp, 50.4 % G + C content, 3, 132 protein-coding genes and 80 RNA genes. Both putative chromate- and sulfate-reducing genes are identified.